Analisis Strategi Mediasi Hakim Bersertifikat dan Non-sertifikat: Studi Kasus Pengadilan Negeri Bangil - m.silahuddin al-maknuni (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Dispute resolution does not always have to be through litigation, but can also be achieved through mediation, which has a legal basis in Perma Number 1 of 2016. Mediation is expected to produce a win-win solution, but practice in the field shows an imbalance between certified and non-certified mediators. This study found differences in strategy: certified judges tend to use a collaborative approach, while non-certified judges are more oriented towards positivism, thus encouraging litigation. In conclusion, mediator certification affects the effectiveness of mediation, emphasizing the importance of improving the competence of judges to strengthen the role of mediation in the judicial system.